Cross-linking agent for reducing fibrillation tendency of lyocell fibers as well as preparation and application of cross-linking agent

By using a crosslinking agent containing sulfonic acid, epoxy and long alkyl chains on the Lycel fibers for finishing treatment, the problem of fibrillation is solved, the wear resistance and feel is improved, and environmentally friendly and industrially applicable effects are achieved.

CN119504657APending Publication Date: 2025-02-25PULCRA SPECIALTY CHEM SHANGHAI CO LTD

Patent Information

Application Number
CN202411660804.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Lycel fibers are prone to fibrillation in wet state, resulting in hairy feathers on the surface of the yarn, which in turn causes problems such as fabric wool, pilling, color change and clothing obsolete.

Method used

A new crosslinking agent is used, which contains sulfonic acid groups, two epoxy groups and long alkyl chains in its molecular structure, and is synthesized by the sulfonation and condensation modification process for finishing the Lycel fibers.

Benefits of technology

It effectively reduces the tendency of fibrillation of Lycel fibers, improves the wear resistance and feel of the fibers, and is simple in process and environmentally friendly, suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143289810000021
    Figure BDA0005143289810000021
  • Figure BDA0005143289810000031
    Figure BDA0005143289810000031
  • Figure BDA0005143289810000051
    Figure BDA0005143289810000051
Patent Text Reader

Abstract

The invention discloses a cross-linking agent capable of reducing the fibrillation tendency of lyocell fibers and a preparation method and application of the cross-linking agent, the cross-linking agent organically combines structural components with multiple functions together through a benzene ring, and the molecular structure not only contains sulfonic acid groups, but also contains two epoxy groups and a long alkyl chain. The preparation method of the cross-linking agent comprises the following steps: (1) sulfonation process: sulfonating cardiac phenol by using concentrated sulfuric acid at 5-10 DEG C to obtain an intermediate; (2) condensation modification process: adding the intermediate obtained in the step (1) into epoxy chloropropane, uniformly mixing to obtain suspension dispersion liquid, heating to 55-65 DEG C under the protection of inert atmosphere, dropwise adding strong alkali alcohol liquid, continuously reacting for at least 1-2 hours at the temperature after dropwise adding is finished, and cooling to room temperature to obtain modified epoxy chloropropane; the obtained product is the cross-linking agent capable of reducing the fibrillation tendency of the lyocell fibers. The application method of the cross-linking agent adopts an independent finishing method or adopts a dyeing and finishing one-bath method to finish lyocell fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lyocell fiber modification and fabric finishing thereof, and in particular to a crosslinking agent for reducing the fibrillation tendency of lyocell fibers, and a preparation method and application thereof. Background Art

[0002] During the spinning process, Lyocell fiber uses safe chemical NMMO (4-methylmorpholine-N-oxide) as solvent. The entire production system forms a closed-loop recycling system with no waste discharge, so it is a truly clean-produced fiber. Compared with viscose fiber, it eliminates the large amount of waste liquid, waste gas and waste residue generated by adding various chemical reagents such as carbon disulfide in fiber production. In addition, since Lyocell fiber products are composed of cellulose, they can be completely biodegraded in a relatively short period of time without any pollution to the environment, so they are known as the "green fiber" of the 21st century.

[0003] However, Lyocell fiber has serious structural defects. It has a unique highly crystalline structure, with weak lateral connections between microcrystals. Lyocell fiber has a high degree of axial orientation, and the lateral bonding force between microfibrils is weak. When the fiber is highly puffed in a wet state, this bonding force is further weakened. In this way, the cortical fibers of Lyocell fiber will fall off under the friction of internal and external factors, and the remaining cortical fibers will crack longitudinally, forming long and uneven fibril hairs. Therefore, Lyocell fiber products are very likely to produce obvious fibrillation in a wet state, and hairiness will be generated on the yarn surface, resulting in Lyocell textiles with shortcomings such as pilling, color change, and old clothes.

[0004] At present, there have been a lot of research on the method of solving the problem of fibrillation of lyocell fibers. The mainstream method is to use a cross-linking agent to post-treat the lyocell fibers or fabrics to achieve the purpose of reducing fibrillation.

[0005] For example, patent document CN1119030A discloses a method for preparing non-fibrillated fibers using polyethylene glycol as a cross-linking agent. However, this method requires long-term high-temperature baking, which will lead to a significant decrease in properties such as fiber strength and elongation.

[0006] Patent document CN103046146A reports that cellulose fibers were dissolved in an ionic liquid composed of anions and cations, and cellulose fibers with excellent anti-fibrillation properties were obtained through dry-jet wet spinning, but industrialization is very difficult.

[0007] Patent document CN104005225A discloses the use of glyoxal as a cross-linking agent to treat lyocell fibers. However, irritating and toxic gases will be volatilized during the production process, which is not conducive to industrial production.

[0008] Patent document CN1147281A uses N-methoxy resin and zero formaldehyde resin as crosslinking agents, while patent document CN103306136A uses a combination of oligomeric polyacids and C2-C6 polyacids as crosslinking agents, etc. All of these methods are difficult to industrially produce crosslinking agents.

[0009] As can be seen from the above, the existing methods all have major defects, some of which are cumbersome to synthesize, some of which are complex in process, and some of which have poor quality of textiles after finishing, etc., which makes these methods very difficult to industrially produce. Summary of the invention

[0010] The invention provides a cross-linking agent for reducing the fibrillation tendency of lyocell fibers, and a preparation method and application thereof.

[0011] The first aspect of the present invention provides a cross-linking agent for reducing the fibrillation tendency of lyocell fibers. The molecular structure of the cross-linking agent contains both a sulfonic acid group and two epoxy groups and a long alkyl chain. The structural formula of the cross-linking agent is as follows:

[0012]

[0013] The second aspect of the present invention provides a method for preparing a crosslinking agent for reducing the fibrillation tendency of lyocell fibers. The synthesis process of the crosslinking agent is as follows:

[0014]

[0015] Wherein, the sulfuric acid is concentrated sulfuric acid.

[0016] In a preferred embodiment, the method for preparing the cross-linking agent comprises the following steps:

[0017] (1) Sulfonation process: sulfonate cardol with concentrated sulfuric acid at 5-10°C to obtain an intermediate;

[0018] (2) Condensation modification process: The intermediate obtained in reaction (1) is added to epichlorohydrin and mixed evenly to obtain a suspension dispersion, which is then heated to 55-65°C under the protection of an inert atmosphere and a strong alkali alcohol solution is added dropwise. After the addition is complete, the reaction is continued at this temperature for at least 1-2 hours. The obtained product is a cross-linking agent that can reduce the fibrillation tendency of lyocell fibers.

[0019] In a preferred embodiment, during the preparation of the cross-linking agent, the reaction raw materials are used in an amount ratio of 1:0.2-0.35:0.9-1.1 based on mass.

[0020] The strong alkali alcohol solution is a solution prepared by dissolving a strong alkali substance in ethanol. The amount ratio of ethanol to the strong alkali substance is 1:1-4 by mass. The strong alkali substance refers to a compound that can completely ionize hydroxide ions (OH-) in an aqueous solution.

[0021] In an optional embodiment, the detailed steps of the sulfonation process are: slowly adding cardol to concentrated sulfuric acid, stirring at 5-10° C. for 1.5-2.5 hours, then pouring into ice water, filtering, and washing the solid matter with a small amount of cold water to obtain an intermediate. The specific operations of "slowly adding" and "a small amount of cold water" can be determined by technicians according to conventional experimental operations and will not be described in detail here.

[0022] In an optional embodiment, during the condensation modification process, uniform mixing can be achieved by stirring, or by other mixing methods such as ultrasonic mixing.

[0023] In an alternative embodiment, the inert atmosphere may be nitrogen.

[0024] In an optional embodiment, the strong alkali alcohol solution is added slowly during the condensation modification process, specifically, at a rate of less than or equal to 30 drops per minute.

[0025] In an optional embodiment, the strong alkaline substance is at least one of sodium hydroxide and potassium hydroxide.

[0026] The third aspect of the present invention provides an application method of the cross-linking agent for reducing the fibrillation tendency of lyocell fibers, characterized in that the application method adopts a separate finishing method or a dyeing and finishing in one bath method to finish the lyocell fibers.

[0027] In a preferred embodiment, the application method of the crosslinking agent adopts a separate finishing method, which is to first immerse the lyocell fiber in a finishing solution at 60-70°C for 5-10 minutes, then pre-treat the fiber at 75-85°C for 100-150s after rolling the fiber dry, and then bake at 125-135°C for 100-150s to solidify and crosslink the fiber, and finally wash it with water at 50°C for 3-5 times, wash it with cold water for 1-3 times, and dry it at 80°C to obtain the anti-fibrillation lyocell fiber. The finishing solution is composed of a crosslinking agent and a dyeing and finishing auxiliary agent, wherein the crosslinking agent is 16-20g / L, the dyeing and finishing auxiliary agent is 3-6g / L, and the pH value of the finishing solution is adjusted to 11-13 with an alkaline substance such as sodium hydroxide.

[0028] In another preferred embodiment, the application method of the cross-linking agent adopts the dyeing and finishing bath method, which is: using a bath ratio of 1:4-10, the lyocell fiber is first evenly circulated in 3-6g / L of the cross-linking agent and 1-3g / L of the dyeing and finishing auxiliary agent, and then the dye is added and evenly circulated, and then sodium sulfate is added, and the operation is continued for 15-25min, and the temperature is raised to 60-80°C, and soda ash is added in multiple times, and the operation is continued for 40-60min, and the fiber is taken out of the cylinder, washed, neutralized, and dried to obtain the anti-fibrillation lyocell fiber. Wherein, the soda ash is a chemical raw material, which refers to anhydrous sodium carbonate. Adding soda ash in multiple times means that the soda ash is added in two or more times.

[0029] Preferably, the dyeing and finishing auxiliary agent is at least one of alkylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate, isomeric alcohol polyoxyethylene ether, sodium dodecyl sulfate, methylnaphthalenesulfonic acid formaldehyde condensate, alkylbenzenesulfonic acid formaldehyde condensate, fatty amine polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether sodium sulfate, fatty alcohol polyoxyethylene ether sodium carboxylate, secondary alkyl sodium sulfonate, sodium methylene dinaphthalene sulfonate, benzylnaphthalenesulfonic acid formaldehyde condensate, and sodium lignin sulfonate.

[0030] The third aspect of the present invention provides an application method of the cross-linking agent for reducing the fibrillation tendency of lyocell fibers (i.e., a finishing method for reducing the fibrillation tendency of lyocell fibers) which can be applied not only to lyocell fibers but also to lyocell fabrics.

[0031] At present, with the advancement of science and technology and the enhancement of environmental awareness, many raw materials can be taken from animals and plants to replace fossil raw materials. The present invention uses cardol as a raw material. Cardol is also called ginkgo biphenol, which exists in cashew nut shells in large quantities, and the content in cashew nut shells is about 15-20%. Modern chemical industry can extract a large amount of high-purity cardol from cashew nut shells. Cardol belongs to a pure bio-based raw material, and its chemical structural formula is as follows:

[0032]

[0033] The present invention starts from cardol and efficiently obtains a cross-linking agent with certain water solubility through a two-step synthesis reaction. The synthesis process of the cross-linking agent is as follows:

[0034]

[0035] The cross-linking agent for reducing the fibrillation tendency of lyocell fiber provided by the present invention is prepared by using cardol taken from cashew nut shell as raw material, that is, based on bio-based raw materials, through a series of treatments and modifications. The cross-linking agent is applied to the anti-fibrillation tendency finishing of lyocell fiber, which is known as the "green fiber" of the 21st century, and can fully reflect the "green" preparation concept of lyocell products.

[0036] In the molecular structure of the cross-linking agent for reducing the fibrillation tendency of lyocell fibers, multiple functional structural components are organically combined through a benzene ring, and the molecular structure contains both a sulfonic acid group and two epoxy groups, as well as a long fatty chain. The present invention simultaneously connects these structural components to a simple benzene ring, and when the lyocell fibers are finished to reduce the fibrillation tendency, a series of synergistic textile finishing effects are produced, including:

[0037] (1) The presence of strong hydrophilic groups (sulfonic acid groups) in the molecular structure of the crosslinking agent can give the crosslinking agent a certain degree of water solubility under alkaline conditions. The water solubility can ensure that the Lyocell fiber is treated more evenly during the finishing process, ensuring that the Lyocell fiber products have better product quality after finishing.

[0038] (2) The presence of epoxy groups in the molecular structure of the crosslinking agent is not only conducive to the water solubility of the crosslinking agent, but also the epoxy groups can be catalytically opened in an alkaline environment, so that they can react with the hydroxyl groups on the lyocell fiber. The presence of the diepoxy groups in the molecular structure can make the fiber form crosslinks after finishing, achieving a good finishing effect of reducing the tendency of fibrillation. Furthermore, this crosslinking agent needs to be finished under alkaline conditions, so it can be used for the separate finishing of lyocell fibers, and can also be used in the same bath for dyeing and finishing, which can improve production efficiency and reduce the discharge of printing and dyeing wastewater.

[0039] (3) Generally, cross-linking finishing of textiles tends to reduce the hand feel of the textiles and make the fiber texture more rigid. Due to the presence of long fatty chains in the molecular structure of the cross-linking agent of the present invention, the hand feel of the Lyocell textile can be maintained or even improved after the Lyocell fiber is finished.

[0040] In addition, the present invention uses a cross-linking agent to post-finish or dye and finish the lyocell fiber in the same bath, the process flow is short, and high-temperature baking of more than 150° C. is not required, which not only has little effect on performance indicators such as the strength and elongation of the fiber itself, but also can give the fiber excellent anti-fibrillation properties; at the same time, the preparation process of the cross-linking agent is simple, the yield is high, and it is green and environmentally friendly, and has broad industrial application prospects and practical application value; in particular, the lyocell fiber has good anti-fibrillation effect after finishing, good washability (wet wear times exceeding 1000 times), little effect on dyeing, no formaldehyde release, and avoids harm to human body and environment. DETAILED DESCRIPTION

[0041] The present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of protection of the present invention. Improvements and adjustments made by those skilled in the art in practical applications according to the present invention still belong to the scope of protection of the present invention.

[0042] Example 1

[0043] Preparation of cross-linking agent:

[0044] (1) Sulfonation process: 200 g of cardol was slowly added to 50 mL of concentrated sulfuric acid, stirred at 10°C for 2 hours, then poured into ice water, filtered, and the solid was washed with a small amount of cold water to obtain the intermediate.

[0045] (2) Condensation modification process: The above intermediate was suspended in about 200 g of epichlorohydrin, heated to 60°C under nitrogen protection, and an ethanol solution of sodium hydroxide (40 g of sodium hydroxide dissolved in 20 mL of ethanol) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 1 hour. After cooling to room temperature, the mixture was poured into ice water and the pH was carefully adjusted to about 5. The precipitated solid was washed with a small amount of cold water to obtain about 240 g of the final product.

[0046] Structural confirmation of cross-linking agent:

[0047] The product was purified and then verified by HR-MS. The HR-MS detection value was 518.2832 and the calculated value was 518.2808. This indicated that the product had the following structure. The other peaks containing carbon chains overlapped with the main peak and were not easy to identify.

[0048]

[0049] Example 2

[0050] Preparation of cross-linking agent:

[0051] Sulfonation process: 200 g of cardol was slowly added to 65 mL of concentrated sulfuric acid, stirred at 10°C for 1.5 hours, then poured into ice water, filtered, and the solid was washed with a small amount of cold water to obtain the intermediate.

[0052] Condensation modification process: The above intermediate was suspended in about 200g of epichlorohydrin, heated to 60°C under nitrogen protection, and an ethanol solution of sodium hydroxide (40g of sodium hydroxide dissolved in 20mL of ethanol) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 1 hour. After cooling to room temperature, the mixture was poured into ice water and the pH was carefully adjusted to about 5. The precipitated solid was washed with a small amount of cold water to obtain about 240g of the final product.

[0053] Structural confirmation of cross-linking agent:

[0054] After purification, the product was verified by HR-MS, and the HR-MS detection value was 518.2839; the calculated value was 518.2808. This indicates that the obtained product has the following structure. The other peaks containing carbon chains overlap with the main peak and are not easy to identify.

[0055]

[0056] Example 3

[0057] Preparation of cross-linking agent:

[0058] Sulfonation process: 200 g of cardol was slowly added to 45 mL of concentrated sulfuric acid, stirred at 5°C for 2.5 hours, then poured into ice water, filtered, and the solid was washed with a small amount of cold water to obtain the intermediate.

[0059] Condensation modification process: The above intermediate was suspended in about 200g of epichlorohydrin, heated to 60°C under nitrogen protection, and an ethanol solution of sodium hydroxide (40g of sodium hydroxide dissolved in 30mL of ethanol) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 1 hour. After cooling to room temperature, the mixture was poured into ice water and the pH was carefully adjusted to about 5. The precipitated solid was washed with a small amount of cold water to obtain about 240g of the final product.

[0060] Structural confirmation of cross-linking agent:

[0061] After purification, the product was verified by HR-MS. The HR-MS detection value was 518.2854 and the calculated value was 518.2808. This indicates that the obtained product has the following structure. The other peaks containing carbon chains overlap with the main peak and are not easy to identify.

[0062]

[0063] Example 4

[0064] Preparation of cross-linking agent:

[0065] Sulfonation process: 200 g of cardol was slowly added into 55 mL of concentrated sulfuric acid, stirred at 5°C for 2 hours, then poured into ice water, filtered, and the solid was washed with a small amount of cold water to obtain the intermediate.

[0066] Condensation modification process: The above intermediate was suspended in about 200g of epichlorohydrin, heated to 60°C under nitrogen protection, and an ethanol solution of sodium hydroxide (40g of sodium hydroxide dissolved in 30mL of ethanol) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 1 hour. After cooling to room temperature, the mixture was poured into ice water and the pH was carefully adjusted to about 5. The precipitated solid was washed with a small amount of cold water to obtain about 240g of the final product.

[0067] Structural confirmation of cross-linking agent:

[0068] After purification, the product was verified by HR-MS, and the HR-MS detection value was 518.2802; the calculated value was 518.2808. This indicates that the obtained product has the following structure. The other peaks containing carbon chains overlap with the main peak and are not easy to identify.

[0069]

[0070] Example 5

[0071] Preparation of cross-linking agent:

[0072] Sulfonation process: 200 g of cardol was slowly added into 50 mL of concentrated sulfuric acid, stirred at 10°C for 2 hours, then poured into ice water, filtered, and the solid was washed with a small amount of cold water to obtain the intermediate.

[0073] Condensation modification process: The above intermediate was suspended in about 220g of epichlorohydrin, heated to 55°C under nitrogen protection, and an ethanol solution of sodium hydroxide (40g of sodium hydroxide dissolved in 25mL of ethanol) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 1.5 hours. After cooling to room temperature, the mixture was poured into ice water and the pH was carefully adjusted to about 5. The precipitated solid was washed with a small amount of cold water to obtain a final product of about 240g.

[0074] Structural confirmation of cross-linking agent:

[0075] After purification, the product was verified by HR-MS. The HR-MS detection value was 518.2902; the calculated value was 518.2808. This indicates that the obtained product has the following structure. The other peaks containing carbon chains overlap with the main peak and are not easy to identify.

[0076]

[0077] Example 6

[0078] Preparation of cross-linking agent:

[0079] Sulfonation process: 200 g of cardol was slowly added into 50 mL of concentrated sulfuric acid, stirred at 10°C for 2 hours, then poured into ice water, filtered, and the solid was washed with a small amount of cold water to obtain the intermediate.

[0080] Condensation modification process: The above intermediate was suspended in about 180g of epichlorohydrin, heated to 60°C under nitrogen protection, and an ethanol solution of sodium hydroxide (40g of sodium hydroxide dissolved in 30mL of ethanol) was slowly added dropwise. After the addition was completed, the reaction was continued at this temperature for 2 hours. After cooling to room temperature, the mixture was poured into ice water and the pH was carefully adjusted to about 5. The precipitated solid was washed with a small amount of cold water to obtain about 240g of the final product.

[0081] Structural confirmation of cross-linking agent:

[0082] After purification, the product was verified by HR-MS. The HR-MS detection value was 518.2819 and the calculated value was 518.2808. This indicates that the obtained product has the following structure. The other peaks containing carbon chains overlap with the main peak and are not easy to identify.

[0083]

[0084] Example 7

[0085] Application examples of crosslinking agents

[0086] A separate finishing method was adopted: the crosslinking agents of Examples 1-6 and sodium dodecylbenzene sulfonate were added to water respectively to prepare 250 mL of finishing solution, wherein the crosslinking agent was 18 g / L and the sodium dodecylbenzene sulfonate was 4 g / L, and the pH value of the finishing solution was adjusted to 11 with sodium hydroxide. The finishing solution was first heated to 65°C, stirred and dissolved, and the lyocell fibers were immersed in the 65°C finishing solution for 10 minutes respectively, and then the fibers were rolled dry and pretreated at 80°C for 2 minutes, and then baked at 130°C for 130 seconds to solidify and crosslink the fibers, and finally washed with 50°C water for 5 times, washed with cold water for 2 times, and dried at 80°C to obtain the anti-fibrillation lyocell fibers after finishing with the crosslinking agents of Examples 1-6.

[0087] The method for determining the degree of fibrillation is to test the mechanical properties and wet abrasion times of the fiber. The specific test methods and performance indicators refer to the standards FZ / T 52019-2018 and T / CCFA01026-2016. In addition, the anti-fibrillation lyocell fiber after finishing was subjected to a hand feel test, among which the hand feel test is a commonly used test index in textiles, which is judged by the tester's touch and feeling. The test results are shown in Table 1 below.

[0088] Table 1

[0089]

[0090] It can be concluded from Table 1 that after cross-linking treatment, the wet abrasion times of Lyocell fiber are significantly improved, far higher than the 550 times specified in the standards FZ / T 52019-2018 and T / CCFA01026-2016, and the strength and elongation of the fiber are also good. At the same time, the test shows that the Lyocell fiber has a good feel, similar to ordinary Lyocell fiber.

[0091] It should be pointed out that the above-mentioned separate finishing method for lyocell fibers can also be applied to lyocell fabrics.

[0092] Example 8

[0093] Application examples of crosslinking agents

[0094] The dyeing and finishing in one bath method was adopted: with a bath ratio of 1:10, the Lyocell fiber was first evenly swirled in 5 g / L of the cross-linking agent and 2.5 g / L of Pingpingjia in Examples 1-6, and then 3.5 g / L of Reactive Yellow 3RS and 2 g / L of Reactive Black KN-B were added respectively, and the fiber was evenly swirled. 40 g / L of sodium sulfate was added and the fiber was continuously swirled for 20 min. The temperature was raised to 60°C, and 20 g / L of soda ash was added three times and the fiber was continuously swirled for 40 min. The fiber was taken out of the vat, washed with water, neutralized and dried to obtain the anti-fibrillated Lyocell dyed fibers dyed and finished in one bath using the cross-linking agent in Examples 1-6.

[0095] The method for determining the degree of fibrillation is to test the mechanical properties and wet abrasion times of the fiber. The specific test methods and performance indicators refer to the standards FZ / T 52019-2018 and T / CCFA01026-2016; for the test effect of the dyeing and finishing bath method, the fiber dyeing uniformity is judged under the D65 light source. In addition, the anti-fibrillation lyocell fiber after finishing was subjected to a hand feel test, among which the hand feel test is a commonly used test indicator in textiles, which is judged by the tester's touch and feeling. The test results are shown in Table 2 below:

[0096] Table 2

[0097]

[0098] It can be concluded from Table 2 that after dyeing and finishing with a cross-linking agent, the wet abrasion times of Lyocell fiber are significantly increased, much higher than the 550 times specified in the standards FZ / T 52019-2018 and T / CCFA01026-2016, and the strength and elongation of the fiber are also good, and the color on the fiber is uniform, and there is no obvious color difference between the fibers. At the same time, after testing, the Lyocell fiber has a good feel, similar to ordinary Lyocell fiber.

[0099] It should be pointed out that the dyeing and finishing in one bath method used for lyocell fiber can also be applied to lyocell fabric.

[0100] Comparative Example 1

[0101] The 200 g of cardol in Example 1 was replaced by 90 g of m-diphenol, and the other operations were the same as in Example 1 to obtain a product with the following structural formula.

[0102]

[0103] Comparative Example 2

[0104] The sulfonation process in Example 1 was removed, and the intermediate in Example 1 was directly replaced with 200 g of cardol in the condensation modification process. The rest was the same as Example 1, and a product with the following structural formula was obtained.

[0105]

[0106] Application experiments of comparative examples 1 and 2

[0107] A separate finishing method was used: referring to the method of Example 7, the products of Comparative Examples 1-2 were used as crosslinking agents respectively, and the detection methods and performance indicators were referred to standards FZ / T 52019-2018 and T / CCFA01026-2016. In addition, the anti-fibrillation lyocell fiber after finishing was subjected to a hand feel test, wherein the hand feel test is a commonly used test index in textiles, and is judged by the tester's touch and feeling. The test results are shown in Table 3 below.

[0108] Table 3

[0109]

[0110] It can be seen from Table 3 that after crosslinking treatment, the wet abrasion times of the Dressel fiber in Comparative Example 1 are significantly increased, and the strength and elongation of the fiber are also similar to those of the crosslinking agent in Example 1. Comparative Example 2 has almost no finishing effect, and the fibrillation tendency is still very serious like the common Dressel fiber. Although the crosslinking agents in Comparative Example 1 and Example 1 have similar dyeing and finishing effects, there is a significant difference in the feel of the finished fibers. The feel of the Dressel fiber in Comparative Example 1 is significantly worse after finishing, and the fiber feels stiff. This is because it lacks long fatty chains in its molecular structure, and long fatty chains have the same application effect as softeners.

[0111] The dyeing and finishing in one bath method was adopted: referring to the method of Example 8, the products of Comparative Examples 1-2 were used as crosslinking agents respectively, and the detection methods and performance indicators were referred to the standards FZ / T 52019-2018 and T / CCFA01026-2016; for the dyeing and finishing in one bath method test effect, the dyeing uniformity of the fiber was judged under the D65 light source. In addition, the anti-fibrillation lyocell fiber after finishing was subjected to a hand feel test, wherein the hand feel test is a commonly used test index in textiles, which is judged by the tester's touch and feeling. The obtained test results are shown in Table 4 below.

[0112] Table 4

[0113]

[0114]

[0115] It can be seen from Table 4 that the wet abrasion times of the Lyocell fiber in Comparative Example 1 after dyeing and finishing in the same bath are significantly improved, the strength and elongation of the fiber are also good, and the color on the fiber is uniform, and there is no obvious color difference between the fibers. These have similar dyeing and finishing effects as the crosslinking agent in Example 1, while Comparative Example 2 has almost no finishing effect. Although the crosslinking agents in Comparative Example 1 and Example 1 have similar dyeing and finishing effects, there is a significant difference in the feel of the finished fibers. The feel of the Lyocell fiber in Comparative Example 1 is significantly worse after finishing, and the fiber feels stiff. This is because it lacks long fatty chains in its molecular structure, and the long fatty chains have the same application effect as softeners.

[0116] In summary, the Lyocell fibers obtained by the single finishing method and the dyeing and finishing in one bath method, although the crosslinking agents of Comparative Example 1 and Example 1 have similar dyeing and finishing effects, the hand feel of the fibers after finishing is significantly different. The hand feel of the Lyocell fibers after finishing in Comparative Example 1 is significantly worse, and the fiber feels stiff. This is because it lacks long fatty chains in its molecular structure, and the long fatty chains have the same application effect as softeners. Comparative Example 2 has almost no finishing effect. After finishing, it has a very serious fibrillation tendency like common Lyocell fibers. This is because it lacks strongly hydrophilic sulfonic acid groups in its molecular structure. Therefore, in the finishing liquid, the water solubility of the crosslinking agent is very poor, and it is dispersed in the water in the form of a suspension, and cannot be crosslinked with the Lyocell fibers in the form of molecules, so that a good anti-fibrillation tendency finishing effect cannot be achieved.

[0117] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0118] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A crosslinking agent for reducing the fibrillation tendency of lyocell fibers, characterized in that: The cross-linking agent has a sulfonic acid group, two epoxy groups and a long alkyl chain in its molecular structure. The structural formula of the cross-linking agent is as follows:

2. A method for preparing a crosslinking agent for reducing the fibrillation tendency of lyocell fibers, characterized in that: The synthesis process of the cross-linking agent is as follows: Wherein, the sulfuric acid is concentrated sulfuric acid.

3. The method for preparing a cross-linking agent for reducing the fibrillation tendency of lyocell fibers according to claim 2, characterized in that: The preparation method of the cross-linking agent comprises the following steps: (1) Sulfonation process: sulfonate cardol with concentrated sulfuric acid at 5-10°C to obtain an intermediate; (2) Condensation modification process: The intermediate obtained in reaction (1) is added to epichlorohydrin and mixed evenly to obtain a suspension dispersion, which is then heated to 55-65°C under the protection of an inert atmosphere and a strong alkali alcohol solution is added dropwise. After the addition is complete, the reaction is continued at this temperature for at least 1-2 hours. The obtained product is a cross-linking agent that can reduce the fibrillation tendency of lyocell fibers.

4. The method for preparing a crosslinking agent for reducing the fibrillation tendency of lyocell fibers according to claim 2 or 3, characterized in that: In the preparation process of the cross-linking agent, the reaction raw materials are used in a ratio of 1:0.2-0.35:0.9-1.1 based on the mass of the cardol, concentrated sulfuric acid and epichlorohydrin.

5. The method for preparing a cross-linking agent for reducing the fibrillation tendency of lyocell fibers according to claim 3, characterized in that: The strong alkali alcohol solution is a solution prepared by dissolving a strong alkali substance in ethanol. The usage ratio of ethanol to the strong alkali substance is 1:1-4 by mass.

6. The method for preparing a cross-linking agent for reducing the fibrillation tendency of lyocell fibers according to claim 3, characterized in that: The detailed steps of the sulfonation process are: slowly adding cardol into concentrated sulfuric acid, stirring at 5-10° C. for 1.5-2.5 hours, then pouring into ice water, filtering, and washing the solid matter with cold water to obtain the intermediate.

7. A method for using the crosslinking agent according to claim 1 or the crosslinking agent prepared by any one of claims 2 to 6 to reduce the fibrillation tendency of lyocell fibers, characterized in that: The application method adopts a separate finishing method or a dyeing and finishing in one bath method to finish the lyocell fiber.

8. The method for applying a crosslinking agent for reducing the fibrillation tendency of lyocell fibers according to claim 7, characterized in that: The application method of the cross-linking agent adopts a separate finishing method, which is to first immerse the lyocell fiber in a finishing liquid at 60-70°C for 5-10 minutes, then roll the fiber dry and pre-treat it at 75-85°C for 100-150s, then bake it at 125-135°C for 100-150s to solidify and cross-link the fiber, and finally wash it with water at 50°C for 3-5 times, wash it with cold water for 1-3 times, and dry it at 80°C to obtain the anti-fibrillation lyocell fiber; wherein the finishing liquid is composed of a cross-linking agent and a dyeing and finishing auxiliary agent, wherein the concentration of the cross-linking agent is 16-20g / L, the concentration of the dyeing and finishing auxiliary agent is 3-6g / L, and the pH value of the finishing liquid is adjusted to 11-13.

9. The method for applying a crosslinking agent for reducing the fibrillation tendency of lyocell fibers according to claim 7, characterized in that: The application method of the cross-linking agent adopts a dyeing and finishing method in the same bath, which is: using a bath ratio of 1:4-10, the lyocell fiber is firstly uniformly circulated in a cross-linking agent with a concentration of 3-6g / L and a dyeing and finishing auxiliary agent with a concentration of 1-3g / L, and then the dye is added and uniformly circulated, and then sodium sulfate is added, and the operation is continued for 15-25min, the temperature is raised to 60-80°C, soda ash is added in multiple times, and the operation is continued for 40-60min, the fiber is taken out of the vat, washed, neutralized, and dried to obtain the anti-fibrillation lyocell fiber.

10. The method for applying a crosslinking agent for reducing the fibrillation tendency of lyocell fibers according to claim 7, characterized in that: Applied to lyocell fibers, or applied to lyocell fabrics.

Citation Information

Patent Citations

  • Method for preparing antigenic fibrillating cellulose fibers by dry-jet wet process

    CN103046146A

  • Cross-linking agent composition, antigen fibrillating solution spinning cellulose fiber, and preparation methods thereof

    CN103306136A

  • Method for reducing lyocell cellulosic fiber fibrillation tendency

    CN104005225A

  • Fibre treatment

    CN1119030A

  • Lyocell fabric treatment to reduce fibrillation tendency

    CN1147281A

Cited By

  • Anti-fibrillation, dyeing and anti-ultraviolet one-bath finishing method for lyocell fibers

    CN121065969A